Clinical manifestations, laboratorial findings and mechanisms of CADASIL: An integrative review (Research, Society and Development, 2022)
This integrative literature review study aimed to analyze the clinical and laboratory findings, in addition to the treatment of case reports of CADASIL from the last 5 years. The database used in the search was PubMed, with the following descriptors: “CADASIL”, “case report”, in addition to the use of the Boolean operator (AND). The final sample was 25 baseline studies. Although CADASIL is caused by a genetic mutation, there was a case in which COVID-19 infection was the beginner of the manifestations of a patient with a previous mutation. In the exams, most have shown damages in MRI, with confluent hypertensive foci, microinfarcts, stenosis and even brain atrophy. Cases were also recorded in which the disease presented parkinsonian syndrome, symptoms of atypical paraplegia, mood alterations and transient ischemic attack. In the study it was perceptive the manifestations in families with this genetic disease. The symptons can be manifested in hetero or homozygous, and may cause mental disorders, headache and stroke. The clinical variety shows its complexity, requiring studies to understand all its pathophysiology.There is no cure for this disease, so its treatments were mainly to control the symptoms.